The expanded amelogenin polyproline region preferentially binds to apatite versus carbonate and promotes apatite crystal elongation - Gopinathan, Gokul; Jin, Tianquan; Liu, Min; Li, Steve; Atsawasuwan, Phimon; Galang, Maria-Therese; Allen, Michael; Luan, Xianghong; Diekwisch, Thomas G. H. (Frontiers in Physiology, 2014)
The transition from invertebrate calcium carbonate-based calcite and aragonite exo- and endoskeletons to the calcium phosphate-based vertebrate backbones and jaws composed of microscopic hydroxyapatite crystals is one of the great revolutions in the evolution of terrestrial organisms. To identify potential factors that might have played a role in such a transition, the vertebrate tooth enamel protein amelogenin was dissected into key domains that were probed for calcium mineral/protein interactions and their ability to promote calcium carbonate and calcium phosphate crystal growth. In initial nanoscale crystal growth studies, the amelogenin peptides from the carboxy-terminus augmented polyproline repeat region but not from the alpha-helical N-terminus nor from the polyproline repeat region alone promoted the formation of thin and parallel crystallites resembling those of bone and initial enamel, while the same proteins in calcium carbonate crystal growth conditions formed fused CaCO3 crystal conglomerates. Our studies also demonstrated that longer polyproline repeat peptides promoted the growth of shorter calcium carbonate crystals with broader basis, contrary to the effect of polyproline repeat element length in earlier apatite mineralization studies. Finally, a parallel series of calcium carbonate and calcium phosphate/apatite protein binding studies revealed that only the carboxy-terminus augmented amelogenin polyproline repeat region and not the N-terminal helical domain bound to calcium phosphates and hydroxyapatite with a high level of affinity, while the amelogenin N-terminus preferentially bound to calcium carbonates. Our data suggest that the rise of apatite-based biominerals in vertebrates might have been facilitated by a rapid evolution